A kinematic model of rotational shot- put technique - Con, M.; Jost, B. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
The purpose of the study was to identify some of the most relevant kinematic parameters defining the competition result in rotational shot-put technique. A biomechanical analysis was carried out on an example of an elite shot-putter, member of the Slovene national team, who had ranked 11th in the finals of the 2004 Olympic Games in Athens. The 3-D video system for kinematic analyses (APAS) was used. A 15-segment model of shot-putter consisting of 18 reference landmarks was defined. The results of the study showed that the top result in rotational technique depended on release velocity, optimal release angle, relation between rotational movement and final acceleration of the shot as well as angular velocity in the elbow and shoulder of the throwing arm. The key phases that ensure the correct rhythm and generate high release velocity of the shot are the following: flight phase, second single support phase and second double support phase.